Teori Kepribadian Behavioristik - Dwi Octaria; Yusi Riksa Yustiana (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This article reviews the development of personality theories within the behavioral framework and their expansion into the social cognitive approach, based on a review of Yustinus Semiun's book